Impact of coronary heart disease on cognitive decline in Alzheimer’s disease: a prospective longitudinal cohort study in primary care - Bleckwenn, Markus; Weyerer, Siegfried (The British journal of general practice, 2017)
Background: Arteriosclerotic disorders increase the risk of dementia. As they have common causes and risk factors, coronary heart disease (CHD) could influence the course of dementia. Aim: To determine whether CHD increases the speed of cognitive decline in Alzheimer’s disease, and to discuss the potential for secondary cardiovascular prevention to modify this decline. Design and setting: Prospective multicentre cohort study in general practices in six cities in Germany. Method: Participants were patients with probable mild-to-moderate Alzheimer’s dementia or mixed dementia (n = 118; mean age 85.6 [±3.4] years, range 80-96 years). The authors assessed the presence of CHD according to the family physicians’ diagnosis. Cognitive performance was measured during home visits for up to 3 years in intervals of 6 months, using Mini Mental State Examination (MMSE) and Clinical Dementia Rating Sum of Boxes (CDR-SoB). The authors also recorded whether patients died in the observation period. Results: At baseline, 65 patients (55%) had CHD and/or a heart condition following a myocardial infarction. The presence of CHD accelerated cognitive decline (MMSE, P<0.05) by about 66%, and reduced cognitive-functional ability (CDR-SoB, P<0.05) by about 83%, but had no impact on survival. Conclusion: The study shows that CHD has a significant influence on cognitive decline in older patients with late-onset dementia. The dementia process might therefore be positively influenced by cardiovascular prevention, and this possible effect should be further investigated.
Gesehen am 04.04.2018